DoE Method for Operating Parameter Optimization of a Dual-Fuel BioEthanol/Diesel Light Duty Engine. (21st January 2015) - Di Blasio, Gabriele; Viscardi, Mauro; Beatrice, Carlo
Abstract : In recent years, alcoholic fuels have been considered as an alternative transportation biofuel even in compression ignition engines either as blended in diesel or as premixed fuel in the case of dual-fuel configuration. Within this framework, the authors investigated the possibility to improve the combustion efficiency when ethanol is used in a dual-fuel light duty diesel engine. In particular, the study was focused on reducing the HC and CO emissions at low load conditions, acting on the most influential engine calibration parameters. Since this kind of investigation would require a significant number of runs, the statistical design of experiment methodology was adopted to reduce significantly its number. As required by the DoE approach, a set of factors (injection parameters, etc.) were selected. For each of them, two levels "high" and "low" were defined in a range of reasonable values. Combining the levels of all the factors, it was possible to evaluate the effects and the weight of each factor and of their combination on the outputs. The results identified the rail pressure, the pilot, and post-injection as the most influential emission parameters. Significant reductions of unburnt were found acting on those parameters without substantial penalties on the global engine performances.